Is a high concentration of high-density lipoprotein cholesterol still relevant? - Hanselim Hanselim (DiscoverSys Inc., 2021)
The importance of cholesterol management, particularly high-density lipoprotein (HDL) cholesterol, has always been believed to be essential in preventing and managing cardiovascular disease (CVD). While HDL has long been accepted as the 'good' cholesterol, various studies have started to challenge this paradigm. Most of these studies found that HDL cholesterol concentrations did not linearly translate into a reduction in CVD risk. There is a suspicion of dysfunctional HDL particles leading to the loss of HDL's cardioprotective function. Some of these dysfunctions were caused by changes in the structure of HDL particles due to an underlying disease or genetic mutations, causing defects in the reverse cholesterol transport (RCT) mechanism and vascular inflammation inhibition. Therefore, therapies that focus on these two mechanisms are expected to be one of the new cornerstones in reducing CVD. Simultaneously, cholesterol efflux capacity (CEC) assay could become the new therapeutic target as it has an inverse correlation with CVD risk regardless of HDL cholesterol concentration, increasing the accuracy in stratifying CVD risk in patients. However, standardization and a more thorough study on CEC assay and various subcellular cholesterol metabolism should be conducted before stepping further.